Africa RISING Baseline Evaluation Survey (ARBES) report for Mali - Howard, P.; Azzarri, Carlo; Haile, Beliyou; Comanescu, M.; Roberts, C.; Signorelli, S. (International Food Policy Research Institute, 2016)
As part of its Feed the future Initiative, the United States Agency for International Development (USAID) supported the development of an innovative research for development project to promote the sustainable intensification of small-scale agriculture in sub-Saharan Africa. Smallscale agriculture represents the main economic activity of the majority of sub-Saharan African population. Therefore, to address global hunger and poverty, the Feed the Future initiative (FtF) developed Africa RISING (Research In Sustainable Intensification for the Next Generation). Africa RISING is an agricultural research program aiming to provide pathways out of hunger and poverty for small holder families, in particular for women and children, through the development of farming systems that can sufficiently improve nutrition and income security, while conserving or enhancing the natural resource pool.